Factors shaping the availability of state-owned, degraded tropical forests for conservation management by NGOs in Ghana, Kenya and Uganda : a thesis presented in partial fulfilment of the requirements for the degree of Master of Environmental Management, Massey University, New Zealand - Ross, Amy Elizabeth (Massey University, 2016)
Degradation of tropical forests contributes to climate change, loss of biodiversity through habitat reduction and ongoing poverty for people who depend on forest resources. This study investigates the current policy environments governing the use of degraded state forests in Ghana, Kenya and Uganda. The research has been undertaken with a view to assisting A Rocha International, an international NGO, in their evaluation of the potential to establish a community conservation project in one or more of these countries. In order to achieve this aim, two key research questions were posed: 1) How do institutional, social and ecological factors enable or constrain NGOs from achieving community conservation goals?; and 2) To what degree are state-owned, degraded tropical forests available for conservation management by NGOs? A multiple case study approach was used for the research. Data was gathered through face-to-face and remote interviews, current policy documents and other secondary sources and personal observation during field trips to Ghana and Kenya. Interviews were conducted with conservation NGO staff, forest-adjacent residents, state forestry officials and district forestry services staff. The policy environments of each country were analysed using a modified version of the social structurationist framework. It was found that the policy environments in Ghana, Kenya and Uganda share many important similarities. Despite the fact that published state policies in all three countries are generally supportive of community conservation initiatives, it is evident that limited policy implementation is likely to have the greatest impact on any proposed project. Socially, pressures on forest governance stemming from corruption, demographic pressures, poverty and energy dependency are common to all three countries. Ecologically, on a broad scale, similar conditions exist across the three countries. Complexities of land tenure, forest benefits distribution and competing interests of actors in Ghana, Kenya and Uganda, can lead to challenges in developing partnerships 3 with local stakeholders in a community conservation project. A key lesson emerging from the study is that time and resources should be invested in addressing this issue. If successful, regardless of the published state forestry policy the conservation NGO may be enabled by the stakeholders to achieve its goals and even influence policy. Faith-based organisations may also have some advantages when it comes to building successful working relationships between project stakeholders. Further lessons relevant to conservation NGO work in the African context may be gleaned from the field of development studies.
Keywords: Forest conservation; Africa, Sub-Saharan; Ghana; Kenya; Uganda; Non-governmental organisations; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Area economics::Forest economics